ALTERNATIVAS PARA LA PROPAGACIÓN in vitro DE PLÁTANO VARIEDAD MAQUEÑO (Musa balbisiana AAB) - Canchignia Martínez, Hayron Fabricio (2008)
The reproduction in vitro is a method adapted for the massive spread of plants, this technology allows and guarantees an efficiency for the commercial exportation of genotipos selected of musáceas since it is the case of banana maqueño. For the aseptic establishment of yolks to level in vitro, the best treatment of disinfection went to 20% of chlorine during 20 minutes + 0.1% of bicloruro of mercury in 10 minutes obtaining 100% of explantes healthy. In the multiplication the best response gave to itself with the treatment 5 mg L-1 of BAP + 1.2 mg L-1 AIA with a value average of 2.5 outbreaks. The phase of development the best result gave to itself in the treatment composed by MS + 20 g saccharose + 1 g of activated coal. The acclimatization and the enraizamiento ex vitro of the vitro you plant one gave the best response in the substratum field land obtained major number of adapted plants, with a length of root 6.1 cm, the substratum shaped by fuzz of rice originated a minor percentage sobrevivencia.